1999
DOI: 10.1557/proc-572-541
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Drain Current Pulsed Response with Microwave Power Output in AlGaN/GaN HEMTs

Abstract: The drain-current response to short ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…First, the gate lag response, which is generally associated with surfaces, 27 shows little dependence on the magnitude of the applied drain-source voltage in GaN high electron mobility transistors ͑HEMTs͒. 28 This is unlike the current collapse mechanism reported here, that requires a high drain-source voltage. Furthermore, silicon nitride passivation of GaN HEMTs has resulted in a change of the gate lag response, 29 with no effect on the observed current collapse behavior.…”
Section: Discussionmentioning
confidence: 64%
“…First, the gate lag response, which is generally associated with surfaces, 27 shows little dependence on the magnitude of the applied drain-source voltage in GaN high electron mobility transistors ͑HEMTs͒. 28 This is unlike the current collapse mechanism reported here, that requires a high drain-source voltage. Furthermore, silicon nitride passivation of GaN HEMTs has resulted in a change of the gate lag response, 29 with no effect on the observed current collapse behavior.…”
Section: Discussionmentioning
confidence: 64%
“…An estimate of the maximum microwave power output obtainable from an FET can be determined from the dc drain characteristics and the operating point. It is frequently observed, however, that the microwave power output of GaN HEMTs is significantly less than that predicted from this estimate [11], [12]. This discrepancy is due in part to trapping effects.…”
Section: Drain Current Transientsmentioning
confidence: 64%
“…Historically, a variety of trapping effects have been observed. These include transconductance frequency dispersion [6], current collapse of the drain characteristics [7], light sensitivity [7], gate-and drain-lag transients [8]- [10], and restricted microwave power output [11], [12]. The research activity that is directed toward understanding and eliminating these effects parallels that of the GaAs-based technology, Manuscript received April 13, 2000; revised September 1, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation with power output with gate lag for AlGaN/GaN HEMTs. The maximum microwave power output at 2 GHz is plotted against the ratio of the pulsed drain current to the dc drain current [54].…”
Section: Surface Trapping In Gan Fetsmentioning
confidence: 99%
“…Binari et al [52]- [54] associated gate lag with the presence of surface trapping in the access region between gate and drain. They found that annealing unpassivated AlGaN/GaN HEMTS at 300 C reduced or eliminated gate lag and dispersion, possibly due to the passivation of surface traps during the annealing process.…”
Section: Surface Trapping In Gan Fetsmentioning
confidence: 99%